Inter-arm blood pressure difference in healthy young adults: a cross-sectional study - Pun, Dilli Bahadur; Chaudhary, Sonam; Shrestha, Prashanna; Thapa, Bobby; Madhikarmi, Nirjala Laxmi (Journal of Physiological Society of Nepal, 2020)
Introduction: Inter-arm difference (IAD) in blood pressure is the difference in the systolic and the diastolic blood pressure between arms of an individual. Studies regarding IAD among elderly, pregnant women, patients with cardiovascular disease and diabetes have been conducted but there are very limited studies carried out among young healthy adults. Thus, this study aimed to investigate the inter-arm blood pressure difference and its association with age, sex, BMI and family history of hypertension among Nepalese healthy young adults. Materials and methods: A cross-sectional study was carried out among 230 students of Kantipur Dental College, Kathmandu, Nepal. Blood pressure was measured using a mercurial sphygmomanometer. Statistical analysis was done using paired t test, chi-square and Pearson’s correlation test using SPSS 16. Results: The absolute mean IAD for SBP was 5.03±3.88 mm Hg and for DBP was 3.84±3.77 mm Hg. There is significant inter-arm difference for SBP (t=4.882, p<0.001) but not for DBP. Inter-arm SBP difference was significantly associated with family history of hypertension (χ2 = 6.41, p=0.01) and positive but weakly correlated with age (r = +0.135, p=0.04). There is no significant association of inter-arm SBP difference with sex and BMI. Meanwhile, there is no statistically significant association of sex, family history of hypertension, age and BMI with inter-arm DBP. Conclusions: There is a significant inter-arm systolic blood pressure difference among the healthy young Nepalese adults and it is associated with the positive family history of hypertension and age.